Low-density lipoprotein receptor-related protein 8 facilitates the proliferation and invasion of non-small cell lung cancer cells by regulating the Wnt/β-catenin signaling pathway. Issue 3 (1st March 2022) - Fang, Zhi; Zhong, Min; Zhou, Ling; Le, Yi; Wang, Heng; Fang, Ziling
ABSTRACT: Low-density lipoprotein receptor-related protein 8 (LRP8) is involved in the development of multiple tumors, including lung cancer. However, the exact mechanism by which LRP8 exerts its oncogenic role in non-small cell lung cancer (NSCLC) remains elusive. Hence, in this study, we aimed to unravel the expression and role of LRP8 in the progression of NSCLC. We used online bioinformatics databases to identify the expression of LRP8 in multiple types of lung cancer. We validated LRP8 expression in NSCLC cell lines and tissues by Western blotting and immunohistochemistry. The functions of LRP8 in NSCLC carcinogenesis and progression were determined using in vitro and in vivo systems. The Wnt pathway activator LiCl was further used to validate the regulatory role of LRP8 in Wnt/β-catenin signaling. We demonstrated that LRP8 was markedly overexpressed in NSCLC tissues and cell lines, and its overexpression significantly correlated with poor clinicopathological characteristics and prognosis. Moreover, LRP8 depletion suppressed cell proliferation, migration, invasion, and epithelial-mesenchymal transition in vitro and impeded tumor growth in vivo . Mechanistically, LPR8 knockdown elicited tumor-suppressive functions by suppressing the Wnt/β-catenin pathway, which was partially reversed by LiCl. Hence, our study revealed that LRP8 facilitates NSCLC cell proliferation and invasion via the Wnt/β-catenin pathway, and thus LRP8 could be a novel therapeutic target for NSCLC. ABSTRACT: uf0001